A comparative study of commercial ELISAs for antibody detection in the diagnostic investigation of Neospora caninum-associated abortion in dairy cattle herds in Uruguay - da Silva Silveira, Caroline (2020)
Bovine abortion causes considerable economic losses to the livestock industry worldwide and is of concern for public health and food safety, given that many abortigenic infectious agents of cattle are zoonotic. Despite its importance, the etiological diagnosis of abortion in cattle is challenging both for veterinary practitioners and laboratory technicians, partly due to the difficulty in recovering aborted fetuses under extensive field conditions for pathological and microbiological diagnostic investigation, and in the early identification of aborted dams. Neospora caninum is a cosmopolitan protozoon identified as one of the main abortigenic agents in cattle worldwide. In this study we propose a comparative seroepidemiological approach for the diagnosis of abortion by N. caninum in dairy cattle. Samples from 12 to 93 cows/heifers with and without recent history of abortion (cases and controls) in four commercial dairy farms were tested. The ratio of controls to cases tested varied from 1:1 to 4.6:1. All samples (n = 230) were analyzed by three commercial ELISA kits for the detection of anti-N. caninum antibodies. In all four dairy farms, the proportion of seropositive cows and/or heifers per kit was significantly higher in the cases than in the controls (Odds Ratios = 5.13 to 36, p = 0.0002 to 0.0485). The agreement among the three kits varied from weak to strong (Coheńs kappa coefficients = 0.58 to 0.83). We conclude that, despite the imperfect agreement between these kits, all of them allowed to arrive at similar conclusions regarding the statistical association between N. caninum seropositivity and abortion, thus representing a useful tool for the diagnostic approach at the population level under field conditions.